Organic syntheses : - Dennis P. Curran (John wiley & sons, 2006)
Organic Syntheses consists of protocols for the synthesis of useful chemical compounds. Each protocol is repeated in the laboratory of one of the editorial board members for accuracy or for missing experimental details prior to publication. For each reaction, source of reagents, waste disposal information, a discussion of the results, references to the primary literature, and an appendix of nomenclature and registry numbers are discussed. Volume 83 continues the tradition of providing significant and interesting procedures, which will prove worthwhile to many synthetic chemists working in increasingly diverse areas.